Cold Rolling Precision Forming of Shaft Parts Theory and Technologies - Song, Jianli; Liu, Zhiqi; Li, Yongtang; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2017)
This book presents in detail the theory, processes and equipment involved in cold rolling precision forming technologies, focusing on spline and thread shaft parts. The main topics discussed include the status quo of research on cold rolling precision forming technologies; the design and calculation of process parameters; the numerical simulation of cold rolling forming processes; and the equipment used in cold rolling forming. The mechanism of cold rolling forming is extremely complex, and research on the processes, theory and mechanical analysis of spline cold rolling forming has remained very limited to date. In practice, the forming processes and production methods used are mainly chosen on the basis of individual experience. As such, there is a marked lack of both systematic, theory-based guidelines, and of specialized books covering theoretical analysis, numerical simulation, experiments and equipment used in spline cold rolling forming processes - all key points that are included in this book and illustrated using tables, 3D photographs and formula derivations.
Introduction -- Principle and Mechanical Analysis on Cold Rolling Precision Forming of Spline -- Process Parameters in the Cold Rolling Precision Forming of Spline -- Numerical Simulation of the Cold Rolling Process of Spline -- Metal Flow Rules and Forming Quality of the Spline Shafts in Cold Rolling Forming -- Mechanism and Process Analysis on the Cold Rolling Forming of Threads -- Process Parameters in the Cold Rolling Forming of Threads -- Numerical Simulation of the Cold Rolling Forming Process of Thread -- Metal Flow Rule and Parameter Optimization of the Cold Rolling Precision Forming of Threads -- Cold Rolling Precision Forming Machines. .
Keywords: Manufactures; Machinery; Mechanics, Applied; Solids; Machines, Tools, Processes; Machinery and Machine Elements; Solid Mechanics